2018
DOI: 10.1021/acschemneuro.8b00282
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Activity of Selected Highly Lipophilic Compounds toward hGAT1 Inhibition. Part II

Abstract: In this paper, we describe the latest results involving molecular modeling and pharmacodynamic studies of the selected highly lipophilic compounds acting by human GABA transporter 1 (hGAT1) inhibition. The chemical interaction of 17 GABA analogues with a model of hGAT1 is described using the molecular docking method. The biological role of GAT1 is related to the regulation of GABA level in the central nervous system and GAT1 inhibition plays an important role in the control of seizure threshold. To confirm tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…It was founded approx. 6.5-7.7 Å due to separation of charged centers [55], which determines the molecule of the interaction with neurons [28]. These conformers are stabilized by intramolecular hydrogen bonds between the nitrogen atom of the amino group and hydrogen of hydroxyl group attached to an ethyl amine carbon atom [55].…”
Section: Hnetmentioning
confidence: 99%
See 2 more Smart Citations
“…It was founded approx. 6.5-7.7 Å due to separation of charged centers [55], which determines the molecule of the interaction with neurons [28]. These conformers are stabilized by intramolecular hydrogen bonds between the nitrogen atom of the amino group and hydrogen of hydroxyl group attached to an ethyl amine carbon atom [55].…”
Section: Hnetmentioning
confidence: 99%
“…A value of 5 Å determines the neuronal and glial blocking effect in selective inhibitors. Computational methods have shown that in an aqueous solution more than 94% of GABA molecules adapt a folded conformation with separation of charged centers below 5 Å [28]. GABA is transported by GAT in a somewhat folded conformation (Figure 5).…”
Section: Hgat1mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, various antagonists of hGAT1, including nipecotic acid, guvacine, proline, pyrrolidine, azetidine and THPO derivatives (Dalby, 2000; Andersen et al, 2001; Clausen et al, 2005; Fülep et al, 2006; Faust et al, 2010; Hellenbrand et al, 2016; Schmidt, Höfner & Wanner, 2017; Lutz et al, 2018; Tóth, Höfner & Wanner, 2018), have been synthesized and pharmacologically tested and optimized using structure–activity relationship (SAR) data. Additionally, several ligand-based strategies including 2D QSAR (Jurik et al, 2013), CoMFA (Zheng et al, 2006) and pharmacophore models (Hirayama, Díez-Sampedro & Wright, 2001; Nowaczyk et al, 2018) have been developed to optimize small molecule inhibitors against hGAT1. However, most of these studies were class specific, focusing on nipecotic acid derivatives (Petrera et al, 2015), Tiagabine analogs (Jurik et al, 2015) and triarylnipecotic acid derivatives (Dhar et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, various antagonists of hGAT1, including nipecotic acid, guvacine, proline, pyrrolidine, azetidine and THPO derivatives (Dalby, 2000;Andersen et al, 2001;Clausen et al, 2005;Fülep et al, 2006;Faust et al, 2010;Hellenbrand et al, 2016;Schmidt et al, 2017;Lutz et al, 2018;Tóth et al, 2018), have been synthesized and pharmacologically tested and optimized using SAR data. Additionally, several ligand-based strategies including 2D QSAR (Jurik et al, 2013), CoMFA (Zheng et al, 2006) and pharmacophore models (Hirayama et al, 2001;Nowaczyk et al, 2018) have been developed to optimize small molecule inhibitors against hGAT1. However, most of these studies were class specific, focusing on nipecotic acid derivatives (Petrera et al, 2015), Tiagabine analogs (Jurik et al, 2015) and triarylnipecotic acid derivatives (Dhar et al, 1994).…”
Section: Introductionmentioning
confidence: 99%